Sustainable masonry blocks: Olive wood waste as substitute for fine aggregates - Marc Antoun; Camille A. Issa; Georges Aouad; Najib Gerges (Case Studies in Construction Materials, 2021)
Due to the high level of pollution generated from the burning of wood waste and the scarcity of natural resources like sand that is causing a change in the eco-system, a greater need to find alternative and innovative solutions is warranted. Thus, this study explores the effect of olive wood waste (OWW) as a replacement for sand in mortar mixes as utilized in concrete masonry blocks. OWW replacement ratios of 25, 50, and 100 % were explored. Properties that were examined included the flexural strength, the compressive strength, and the heat of hydration. The compressive strength and flexural strength were analyzed at 3, 7, 14, 28, and 40 days, while the flowability was measured immediately following the fresh mixing process, and the heat of hydration was measured for 48 h after casting. The results indicated that 25 and 50 % of standard sand replacement by OWW yielded a flexural strength that exceeded the reference mix, while reducing the heat of hydration, and maintaining an acceptable compressive strength for non-structural applications such as sidewalks, borders, ditches, filler blocks, and masonry blocks.